2020
DOI: 10.1177/0898010120961579
|View full text |Cite|
|
Sign up to set email alerts
|

Peppermint Essential Oil for Nausea and Vomiting in Hospitalized Patients: Incorporating Holistic Patient Decision Making Into the Research Design

Abstract: Aims This study examined nausea and vomiting (N/V) in hospitalized patients following the use of inhaled peppermint essential oil (aromatherapy) compared to combined aromatherapy/antiemetics or antiemetics alone. Method and Materials A total of 103 hospitalized patients were offered one of three options to control N/V. Patient choice was considered in the holistic trial design so that patients were not denied either the essential oil or antiemetics. Patients rated nausea 0 to 10 on the Edmonton Symptom Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…25 Aromatherapy using other agents has also been investigated in holistic journals. Peppermint alone [26][27][28] or in combination, 29 as well as ginger [29][30][31] seem to be promising interventions. However since these aren't readily available in most clinical settings, they will not be included in the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…25 Aromatherapy using other agents has also been investigated in holistic journals. Peppermint alone [26][27][28] or in combination, 29 as well as ginger [29][30][31] seem to be promising interventions. However since these aren't readily available in most clinical settings, they will not be included in the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…In a single-blind, randomized, controlled trial, it was shown that inhalation of 0.2 mL of 10% and 30% peppermint essential oil in each of the study groups significantly reduced the severity of nausea after the intervention [ 112 ]. In many clinical trials, inhalation of peppermint oil has been shown as effective in reducing the perceived severity of postoperative nausea and, according to the authors, should be considered as a first-line treatment that can be used quickly [ 113 , 114 , 115 , 116 , 117 ]. In addition, peppermint oil aromatherapy offers a rapid onset of action, ease of administration, and the absence of any serious side effects [ 118 ].…”
Section: Herbal Medicines Used To Counteract Some Pregnancy-related Symptoms (Eg Nausea and Vomiting Dizziness And Headache And Memory Lomentioning
confidence: 99%
“…10 Aromatherapy can be administered in different ways such as through massage, medicated baths, skin absorption, or inhalation. 11 Inhales aromatherapy is a popular method in complementary medication. This medication influences the limbic system and makes individuals relaxed.…”
Section: Introductionmentioning
confidence: 99%